Best practices in the field of returnee entrepreneurship - Raluca Mariana Grosu (Amfiteatru Economic Journal, 2015)
Romania, an important provider of immigrants - especially for member states of the European Union - has remarkable potential for developing returnee entrepreneurship. Observing this context, through this paper I aim to highlight means of encouraging this phenomenon in Romania, one of the main objectives referring to the development of a best practice guide in order to promote and sustain returnee entrepreneurship. Based on an intensive process of literature review, following the experience of other countries with a high degree of experience in this field, I created a model that illustrates a series of specific features displayed by this phenomenon, as well as a best practice guide. This guide mainly outlines a series of directions regarding financial, legislative, institutional, and educational aspects. Through this paper, I aim to bring a contribution to the development of the scientific literature in the field of returnee entrepreneurship and to raise awareness among policy makers on the complexity and importance of this phenomenon. Furthermore, by detailing the components of this model in Romania and by presenting the best practice guide, this paper may represent an important starting point in developing a national strategy for encouraging emigrants' return and the development of entrepreneurial activities among them.
Keywords: J60; M10; 330; entrepreneurship; returnee entrepreneurship; best practices; Romania; international migration; emigration